Symmetrization and sharp Sobolev inequalities in metric spaces - Milman, Mario; Kališ, Jan (Revista Matemática Complutense, 2009)
We derive sharp Sobolev inequalities for Sobolev spaces on metric spaces. In particular, we obtain new sharp Sobolev embeddings and Faber-Krahn estimates for H¨ormander vector fields.
Keywords: Sobolev; Embedding; Metric; Vector fields; Symmetrization